KAJIAN KENAKALAN REMAJA PERPEKTIF AL QUR’AN DAN HADITS - Rofiah Rofiah (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2023)
Today's moral emerosotanism is already really worrying. Honesty, truth, justice, help and compassion are already covered by misappropriation, deception, oppression, mutual harm and harm to each other. This study aims to describe and analyze the factors of juvenile delinquency, and verses of adolescent social ethics from the perspective of the Qur'an the approach used is qualitative and descriptive with the type of research literature study, and the source of data used is Al Quran, books, articles and works ilmiah l it ai related to the focus of the research. The results of this study are: (1) There are two factors of juvenile delinquency, namely Internal and external factors, internal actors include; personal psychology, family, identity crisis, and weak self-control whereas external actors include; community environment and friends ( 2) Verses of Adolescent Association Ethics The perspective of the Qur'an is in the Qur'an Surah Yusuf verse 30 and verse 36